Jejak Intelektual Ulama Nusantara dalam Tradisi Penafsiran Al-Qur’an dari Klasik hingga Kontemporer (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the intellectual footprint of Nusantara scholars in the tradition of Qur'anic interpretation from classical to contemporary times. This study is motivated by the importance of understanding the role and contribution of Nusantara scholars in building a distinctive and contextual style of interpretation with local culture. The purpose of this study is to trace the development of methods, styles, and approaches to interpretation used by scholars from time to time. The method used is qualitative with a literature study approach through analysis of exegetical works such as Tarjuman al-Mustafid by Abdur Rauf as-Singkili, Tafsir Al-Munir by Nawawi al-Bantani, Tafsir Al-Furqon by Al-Hasan, Tafsir Al-Qur'an Karim by Prof. Dr. H. Mahmud Yunus, Tafsir Al-Azhar by Hamka, to Tafsir al-Mishbah by M. Quraish Shihab. The research results show that during the classical period, interpretation focused on spirituality and spirituality, while in the modern and contemporary eras, interpretations have developed that emphasize the maqasid al-shari'ah (purpose of law). They focus not only on literal meaning but also on universal wisdom and objectives. This development reflects the continuity between the global Islamic scholarly tradition and the local socio-cultural realities of the Indonesian archipelago. Interpretations of the Quran by Indonesian scholars not only enrich the global Islamic heritage but also demonstrate that Islam is capable of dialogue with cultural and contemporary contexts without losing its universal values.